The Role of Innate Immunity in Natural Elite Controllers of HIV-1 Infection - Shi, Yuting; Su, Jinming; Chen, Rongfeng; Wei, Wudi; Yuan, Zongxiang; Chen, Xiu; Wang, Xinwei; Liang, Hao; Ye, Li; Jiang, Junjun (Frontiers in Immunology, 2022)
The natural process of human immunodeficiency virus type 1(HIV-1) infection is characterized by high viral load, immune cell exhaustion, and immunodeficiency, which eventually leads to the stage of acquired immunodeficiency syndrome (AIDS) and opportunistic infections. Rapidly progressing HIV-1 individuals often die of AIDS several years after infection without treatment. The promotion of ART greatly prolongs the survival time of HIV-infected persons. However, some patients have incomplete immune function reconstruction after ART due to latent storage of HIV-infected cells. Therefore, how to achieve a functional cure has always been the focus and hot spot of global AIDS research. Fortunately, the emergence of ECs /LTNPs who can control virus replication naturally has ignited new hope for realizing a functional cure for AIDS. Recently, a special category of infected individuals has attracted attention that can delay the progression of the disease more rigorously than the natural progression of HIV-1 infection described above. These patients are characterized by years of HIV-1 infection, long-term asymptomatic status, and normal CD4+T cell count without ART, classified as HIV-infected long-term nonprogressors (LTNPs) and elite controllers (ECs). Numerous studies have shown that the host and virus jointly determine the progression of HIV-1 infection, in which the level of innate immunity activation plays an important role. As the first line of defense against pathogen invasion, innate immunity is also a bridge to induce adaptive immunity. Compared with natural progressors, innate immunity plays an antiviral role in HIV-1 infection by inducing or activating many innate immune-related factors in the natural ECs. Learning the regulation of ECs immunity, especially the innate immunity in different characteristics, and thus studying the mechanism of the control of disease progression naturally, will contribute to the realization of the functional cure of AIDS. Therefore, this review will explore the relationship between innate immunity and disease progression in ECs of HIV-1 infection from the aspects of innate immune cells, signaling pathways, cytokines, which is helpful to provide new targets and theoretical references for the functional cure, prevention and control of AIDS, and development of a vaccine.